(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
The socioeconomic transformations of the last decade, which have shaped shifts in educational and scientific paradigms, have naturally led to the need to combine education with individual health, the foundations of which, as is generally recognized, are laid in school and developed, reinforced, and refined during college, primarily through physical education and sports.